Sense of Filial Obligation and Caregiving Burdens Among Chinese Immigrants in the United States. (12th August 2019) - Guo, Man; Kim, Sohyun; Dong, XinQi
Abstract : BACKGROUND/OBJECTIVES: Focusing on Chinese immigrants, this study examined (1) whether filial obligation, the core social norm in the Chinese culture, is related to caregiving burdens; and (2) whether level of acculturation of the caregivers moderates the above relationships. DESIGN: Cross‐sectional. SETTING: Chicago, Illinois. PARTICIPANTS: A purposive sample of 393 Chinese adult immigrants who were primary caregivers of parents aged 60 years or older. MEASURES: Sense of filial obligation was captured by felt responsibility toward parents in six domains (respect, make happy, care, greet, obey, and provide financial support). Caregiving burdens were measured by the Caregiver Burden Inventory. Acculturation was measured by 12 questions about respondents' language preference in different settings and ethnicity of individuals they interact with. RESULTS: A stronger sense of filial obligation was significantly associated with lower levels of developmental (β = −.15), emotional (β = −.18), social (β = −.20), and physical (β = −.10) burdens. For subjective burdens (developmental, social burdens), such a protective effect of filial obligation was stronger among caregivers with lower acculturation levels. For more objective burdens (time‐dependent, physical burdens), stronger filial obligation was actually associated with greater burdens among caregivers with higher acculturation levels. CONCLUSION: Programs focusing on celebrating the cultural heritage of immigrants and improving the relationship between the parents and children may be helpful to reduce caregiving burdens. Intervention programs that help Chinese immigrant caregivers to find the most appropriate way to balance traditional and new social norms are important to provide successful care to aging Chinese immigrants. J Am Geriatr Soc 67:S564–S570, 2019.